DISCUSSING THE COMMON(S) IN NEOLIBERAL CAPITALISM: FROM ONTOLOGY TO POLITICS - Saidel, Matías (Fragmentos de Filosofía, 2023)
This article intends to think the relationship between neoliberal capitalism and the common(s). First, it ties to define the common both in ontological and olitical terms, stressing the similarities and differences between the common, commons and common goods. Then, it characterizes their relationship with neoliberal capitalism in terms of dispossession, expropriation and configuration. Finally, it discusses if the common can be thought as an alternative form of cooperation and self-government with regards to neoliberalism and to what extent it can be posed as a complete alternative to the state.